Biochemical alterations of red rice cultivated at soil water levels and organomineral fertilization - Dutra, Katia Otilia Gomes; Irineu, Toni Halan da Silva; Véras, Mário Leno Martins; Figueredo, Janailson Pereira de; Silva, Josimar Nogueora da; Andrade, Raimundo; Meneses, Carlos Henrique Salvino Gadelha (Comunicata Scientiae, 2018)
Red rice is cultivated mainly by small farmers in the northeastern region of Brazil, a region characterized by water scarcity, that is why studies like those are needed aiming to save water without undermining crop cultivation. In this context, the objective was to evaluate in the red rice crop with application of silicon and biofertilizer: soil water levels, growth, productivity and biochemical parameters. The experiment was conducted in a protected environment at the State University of Paraíba, in the municipality of Catolé do Rocha-PB. The design was completely randomized, in the factorial arrangement 4 x 2 x 2, with four replications. The treatments consisted of four levels of water in the soil (70, 80, 90 and 100%), with silicon and without silicon application, with biofertilizer and without biofertilizer application. Rice responded significantly to available water levels in the soil for all variables studied. Silicon and biofertilizer contributed to a better tolerance of rice to water stress. Organomineral fertilization increased the concentrations of the Proline, Glycine betaine and Trehalose osmoregulators. The lowest availability of water provided an increasement in the red rice osmoregulators concentration, that act as a plants protector against cell damages.